Radiofrequency Ablation of a Solitary Liver Metastasis Complicated by Colonic Perforation - Korutz, Alexander W. (Thieme Medical Publishers, 2011)
Radiofrequency ablation is used for the treatment of primary liver malignancies and liver metastases. In this case, the authors performed percutaneous radiofrequency ablation of a solitary esophageal carcinoma metastasis within the left hepatic lobe. Following the procedure, the patient developed a colonic perforation with a large right upper quadrant abscess. Although the abscess nearly resolved after intravenous antibiotics and percutaneous drainage, the patient ultimately developed a colocutaneous fistula that required surgical excision and right hemicolectomy. The risks for developing this complication as well as measures to minimize this risk are discussed.